Ksiądz Józef Piekieliński (Piekielny) (1897–1942), ofiara obozu koncentracyjnego w Dachau - Szkutnik, Piotr (Biuletyn Szadkowski, 2012)
Father Józef Piekieliński was born in 1897 in Szadek, where his family lived. After finishing the Theological Seminary in Włocławek he worked as catechist and curate in a number of parishes in Kujawsko-Kaliska diocese, and then in Częstochowa diocese. In the period 1932–1941 he was the parish priest in Jaworzno near Wieluń. During massive arrests of Polish clergy by Germans in 1941he was imprisoned in the concentration camp in Dachau, where he died in 1942.